Omega‐3 Marine Fatty Acid Supplementation to Healthy Subjects Interacts With Moderate Physical Activity to Provide a Cardiovascular Healthier Lipoprotein Subclass Profile - Kvalheim, Olav M.; Rajalahti, Tarja (Journal of chemometrics, 2024)
ABSTRACT This work investigates the impact of marine omega‐3 and physical activity and their interaction on cardiometabolic health as expressed by the serum lipoprotein profile. Using an experimental design that allows for the possibility of interaction, we performed a 6‐week intervention on 44 middle‐aged women living in Western Norway. The women were randomly divided into four groups: one control group with no intervention, a second group performing sessions of moderate intensity three times per week, a third group taking daily supplements of omega‐3 marine fatty acids, and a fourth group combining the interventions for Groups 2 and 3. The difference in the lipoprotein profiles after the intervention from baseline were assessed for statistical significance by comparing groups 2, 3 and 4 with Group 1 using two‐tailed t‐test corrected for multiple testing and selectivity ratios calculated from the discriminatory component in validated partial least squares discriminant models. The results from the univariate and multivariate analyses were qualitatively equivalent: Only the women combining moderate physical activity and omega‐3 supplementation, revealed statistically significant differences in their lipoprotein profile compared to the nonintervention control group. The pattern of change in the lipoprotein profile is associated with improved cardiometabolic health. Use of the design matrix to predict this pattern revealed that the interaction between omega‐3 supplementation and physical activity played a major role in inducing this change. The recognition of the influence of this interaction may be a step towards resolving the long‐lasting debate of the role played by omega‐3 for preventing cardiovascular unhealth.